Ocular adnexal manifestations of neuroendocrine neoplasms: a case report and a major review. (2nd November 2021) - Hatsis, Alexander J.; Henry, Roger K.; Curtis, Mark T.; Bilyk, Jurij R.; Sivalingam, Meera D.; Eagle, Ralph C.; Milman, Tatyana
ABSTRACT: Purpose: To describe a patient with orbital neuroendocrine neoplasm (NEN)/carcinoid tumor and to review the clinical presentation, systemic work-up, histopathologic features, and outcome of all previously reported ocular adnexal (OA) NENs. Methods: A systematic literature review. PubMed/MEDLINE and Google Scholar databases were searched for all well-documented cases of OA NENs. Results: Final analysis yielded 94 patients with OA NENs, 50 females (53%) and 44 (47%) males with an average age of 63 years (range 14–86). Of 91 patients with known information, the most common presenting signs were proptosis (56/91, 61%) and visual disturbances (42/91, 47%), induced by a mass most commonly associated with an extraocular muscle (49/63, 78%). The majority of tumors (88/94, 94%) were metastases, most commonly from the gastrointestinal tract (52/88, 59%). OA NEN metastasis presented following detection of primary tumor in 73/94 (78%) patients (median time to metastasis 36 months, range 0–288 months) and as an initial manifestation of disease in 15/94 (16%) patients (median time to primary detection 18 months, range 1–108 months). Systemic work-up included extra-OA NEN biopsy (37/54, 69%), multimodal imaging (42/54, 78%), and other laboratory studies (32/54, 59%). Resection with or without adjuvant chemotherapy, radiotherapy, and biologics was the most common intervention for OA NENs (36/82, 44%). Of 67 patients with available follow-up, the median survival was 108 months (95% CI 55–161 months) and the absolute 5-year survival rate was 68%. Conclusions: OA NENs are almost exclusively metastases and can precede detection of primary tumor by many months, requiring appropriate diagnostic work-up.